Klasifikasi Data Gempa Bumi di Pulau Sumatera Menggunakan Algoritma Naïve Bayes - Duha, Tobias; Laia, Mitranikasih; Huda, Amirudin Khorul; Jasuma, Agung (LPPM Universitas Nias Raya, 2023)
Indonesia is one of the countries located in the Pacific Ring of Fire, where three tectonic plates meet. This makes Indonesia very vulnerable to natural disasters such as earthquakes, volcanic eruptions, and tsunamis. These natural phenomena occur very frequently, as evidenced by events such as those that have occurred on the island of Sumatra. This study aims to classify earthquake data in the Sumatra Islands based on hypocenter using the Naive Bayes Algorithm. The study uses earthquake datasets specifically from the Sumatra Islands, which are divided into training and testing data. The results of the study indicate that classification can be performed using the Naive Bayes Algorithm based on three categories, ranging from shallow earthquakes, moderate earthquakes, to deep earthquakes.